Investigation of Structural and Dielectric Behavior of Ba0.7Gd0.3MoxFe12-xO19 (Where x = 0.02) Hexaferrite Ceramics - Agnihotri, Pratiksha; Kumar, Abhijeet; Rai, Radheshyam; Singh, Budhendra Kumar (Ferroelectrics. Letters section, 2023)
Multiferroic ceramic composites of (Ba 0.7 Gd 0.3 Mo x Fe 12-x O 19 were prepared by using the solid-state reaction method with mol% fractions of x = 0.02, The preliminary structural studies carried out by X-ray diffraction at room temperature. It reveals that the samples have a hexagonal structure ferrite phase. The impurity phase of x-Fe 2 O 3 appear at 32 ∼ 34 degree. Debye-Scherer and Williamson-Hall method were used to analysis for peak broadening Ba 0.7 Gd 0.3 Mo x Fe 12-x O 19 (where x = 0.02). Dielectric graphs show that curie temperature shifted towards the high temperature with increasing the frequency. the dielectric transitions at 200-300 °C.